2015
DOI: 10.5851/kosfa.2015.35.6.757
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Meat Quality Characteristics of the Sous-vide Cooked Chicken Breast during Refrigerated Storage

Abstract: This study was performed to investigate the changes in meat quality characteristics of the sous vide cooked chicken breast during refrigerated storage at 4℃ for 14 d between before and after sous-vide cooking. Cooking loss and shear force were significantly increased, whereas expressible drip was significantly decreased along with reduction in the water holding capacity in both of two groups. Redness of meat juice was significantly (p<0.05) increased during storage, and considerably increased in the refrigerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 30 publications
(31 reference statements)
2
27
2
1
Order By: Relevance
“…Except for marginal differences, the WBSF values obtained from the psoas minor muscle of ewes (34.2 ± 1.87) from the Dhone Merino were similar to those obtained from the musculus longissimus thoracis et lumborum (33.9) and semimembranosus (34.9) of castrated Tanzanian long fat-tailed sheep (Shirima et al, 2013). Higher WBSF values from most of the samples from ewes could be attributed to the presence of a strong adhesive force in the connective tissues, low water-holding capacity, and an increase in cooking loss (Warner et al, 2007;Hong et al, 2015). However, Purslow (2005) found that strong connective bonds in the muscles of older animals could impose higher resistance to denaturation of collagen during cooking.…”
Section: Discussionsupporting
confidence: 69%
“…Except for marginal differences, the WBSF values obtained from the psoas minor muscle of ewes (34.2 ± 1.87) from the Dhone Merino were similar to those obtained from the musculus longissimus thoracis et lumborum (33.9) and semimembranosus (34.9) of castrated Tanzanian long fat-tailed sheep (Shirima et al, 2013). Higher WBSF values from most of the samples from ewes could be attributed to the presence of a strong adhesive force in the connective tissues, low water-holding capacity, and an increase in cooking loss (Warner et al, 2007;Hong et al, 2015). However, Purslow (2005) found that strong connective bonds in the muscles of older animals could impose higher resistance to denaturation of collagen during cooking.…”
Section: Discussionsupporting
confidence: 69%
“…Many consumers in Korea prefer chicken legs than chicken breast when buying or consuming chicken products, as cooked breast meat tends to exhibit a tougher and more crumbly texture than cooked chicken legs ( Hong et al., 2015 ). These characteristics of chicken breast can be improved using the sous-vide cooking method.…”
Section: Introductionmentioning
confidence: 99%
“…Оther studies (Baldwin 2011) proved that broccoli, whole and sliced, boiled directly in water, may lose (28%) and under pressure (62%) of their color, and at 5 day-storage lose 9.4% and 7.3% of their color. The preparation of vegetables with a high starch content can also be carried out at lower temperatures (80ºС) since carrot cooking can be used as it provides a uniform dissolution of the pectin and a uniform culinary readiness (Hong et al 2015). Care should be taken of the thickness of the carrot layer to be processed, as well as the difference in it is optimal for the starch gelling (Garcıa-Segovia et al 2007).…”
Section: "Sous-vide" Cooking Of Vegetablesmentioning
confidence: 99%
“…In vegetables rich in starch, such as beans, peas, lentils, maize, potatoes, the application of the "sousvide" method leads to the formation of a uniform culinary readiness when finely pasteurized starch in their composition (Baldwin 2011). Hong et al (2015) reported that when boiling beans at 90ºС, it absorbed the same amount of water as it did at room temperature for 16 hours. The quality of water used for cooking beans effected on the degree of boiling.…”
Section: "Sous-vide" Cooking Of Vegetablesmentioning
confidence: 99%
See 1 more Smart Citation